Location based reliability differentiation service for WSN - ZENG Yong1; MA Jian-feng1 (Tongxin xuebao)
How to design reliability differentiated service for missions with different reliability requirements becomes one of hot topics in wireless sensor networks. Combined with location-based routing mechanism, a quantified model without full network topology was proposed to evaluated reliability. By introducing a virtual reference point, the data transfer was limited in a specified area. The reliability function of the area was given. A detailed analysis shows that the function increases quadratically with the distance between the source node and the reference node. Based on the above conclusion, a reliability differentiated service mechanism was proposed. Simulation results show the efficiency of proposed mechanism.